Designing Quantum Capacitive Peptide Interfaces for Electroanalytical Applications - Brandaõ, Sarah T.R. [UNESP]; dos Santos, Adriano [UNESP]; Bueno, Paulo R. [UNESP]; Cilli, Eduardo M. [UNESP] (American Chemical Society (ACS), 2023)
Redox-active moieties assembled on metallic interfaces have been shown to follow quantum mechanical rules, where the quantum capacitance of the interface (directly associated with the electronic structure of the redox-active moieties) plays a key role in the electron transfer dynamics of the interface. Modifying these interfaces with biological receptors has significant advantages (simplifying molecular diagnostics methods, reducing size, time, and cost while maintaining high sensitivity), enabling the fabrication of miniaturized electroanalytical devices that can compete with traditional ELISA and RT-PCR benchtop assay methods. Owing to their intrinsic characteristics, the use of peptide-based redox-active moieties is a promising chemical route for modifying metallic surfaces, resulting in a high quantum capacitive signal sensitivity. In the present work, different ferrocene-tagged peptides with a structure of Fc-Glu-XX-XX-Cys-NH2 (XX = serine, phenylalanine, glycine) were used to form self-assembled monolayers on gold. The feasibility of using these interfaces in an electroanalytical assay was verified by detecting the NS1 DENV (Dengue Virus) biomarker to compare the efficiency of peptide structures for biosensing purposes. Parameters such as the formal potential of the interface, normalized electronic density of states (DOS), quantum capacitance, and electron transfer rate constants were obtained for Ser-, Phe-, and Gly-peptides. The Gly-peptide structure presented the highest analytical performance for sensing NS1 with a sensitivity of 5.6% per decade and the lowest LOD (1.4 ng mL-1) and LOQ (2.6 ng mL-1), followed by Phepeptide, whereas Ser-peptide had the lowest performance. This work demonstrates that the use of peptides to fabricate a self-assembled monolayer as a biosensor component has advantages for low-cost point-of-care diagnostics. It also shows that the performance of the sensing interface depends strongly on how the chemistry of the surface is designed as a whole, not only on the redox-active group.